Structure and change in a local holiday resort: Peaceful Bay, on the southern coast of Western Australia - Selwood, J.; Curry, George; Koczberski, Gina (Routledge, 1995)
Most of the literature dealing with holiday resorts focuses on high impact, mass market destinations like the south-east coast of Queensland, Bali and other major tourist attractions. Relatively little attention is given to the low profile holiday resort patronised by local holiday-makers taking a relaxed vacation with family and friends. Such resorts may not appear important to tourism researchers as they have a lower impact on their host communities, they do not provide much in the way of facilities or packaged entertainment for the traveller, and they are not featured in the glossy travel literature. Nevertheless, low profile holiday resorts have an important function, sastisfying a legitimate market niche. Moreover, perhaps unfortunately for their traditional patrons, these resorts eventually tend to be 'discovered' by a wider clientele and their intrinsic character changes.This paper examines one such community resort: Peaceful Bay, on the south-west coast of Western Australia. This small settlement of some 200 cottages has been until recently quite isolated and mostly frequented by the local farm population for short holiday breaks. However, with the increasing accessibility and popularity of the region, there are pressures for change. Community structure is in flux and the settlement undergoing expansion. Its future is uncertain, but its transformation into something different appears inevitable.